Implementation of Marketing Plans in Abrasion Resistance Plate Steel Stockist and Fabrication Companies in Indonesia - Giyanto; Rhian Indradewa; Edi Hamdi (Syntax Idea)
This research aims to investigate and analyze the implementation of marketing plans at Abrasion Resistance Plate stockist and steel fabrication companies in Indonesia. Abrasion Resistance Plate is a material that is needed in various industries, especially in construction and manufacturing, because of its extraordinary wear-resistant properties. Implementation of an effective marketing plan can be a key factor in a company's success in a competitive market. This study was conducted by analyzing the marketing strategies used by companies in marketing their Abrasion Resistance Plate products. The research methodology involved analysis of primary and secondary data, including interviews with company management, customer surveys, and literature reviews. The results of this research provide in-depth insight into the marketing strategies used by this company, including market segmentation, pricing, promotion, and distribution. The findings of this research will provide valuable guidance for similar companies in the Abrasion Resistance Plate steel industry and also contribute to a better understanding of the dynamics of the steel market in Indonesia. Apart from that, the results of this research can also be a basis for these companies to improve and optimize their marketing plans in order to increase their competitiveness in the market.